Off-balance sheet income activities for islamic and conventional banks / Masturah Ma'in, Latifah Syaqirah Misni and Siti Sarah Mat Isa. - Ma'in, Masturah; Misni, Latifah Syaqirah; Mat Isa, Siti Sarah (Universiti Teknologi Mara Selangor, 2015)
The aim of this study is to investigate the determinants of off-balanced sheet income activities, considering the bank-specific and macroeconomic factors as independent variables in Islamic and conventional banks in Malaysia. This study utilizes 16 Islamic banks and 14 conventonal banks panel data from 2008-2013 and 2002-2013 respectively. The result shows that the determinants of off-balance sheet activities in Islamic banks in Malaysia are bank's size (TA), bank's profitability (NP), and interest rate (INT). While, the determinants of off-balance sheet activities in conventional banks are bank's size (TA), bank's profitability (NP) and the Real Gross Domestic Product (RGDP).